Determination of Competitive Advantages: Analysis of Values, Leadership and Supply Chain Management - Ahmad Munawar, Niknik (Dinasti Publisher, 2022)
Literature Review Article Determination of Competitive Advantages: Analysis of Values, Leadership, Supply Chain Management is a scientific article that aims to build a research hypothesis of the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Values are related to Competitive Advantages; 2) Leadership is related to Competitive Advantages; 3) Supply Chain Management relates to Competitive Advantages. Apart from these 3 exogenous variables that affect the endogenous Competitive Advantages, there are still many other factors including vision, six sigma and ISO compliance.